An Update on Myocarditis in Forensic Pathology - Jessica Falleti; Pasquale Orabona; Maurizio Municinò; Gianluca Castellaro; Giovanna Fusco; Gelsomina Mansueto (Diagnostics, 2024)
In forensic medicine, myocarditis is a complicated topic in the context of sudden death and medical malpractice. A good knowledge of the etiopathology, histopathology, and available literature are both indispensable and essential for the correct management and evaluation of the causal link. Some agents, which are rarely lethal for humans, are not necessarily related to death from myocarditis, even if an infection in other organs such as the gastrointestinal tract is documented. The diagnosis of the causes of death is often difficult and confusing. In some cases, the hypothetical diagnosis of myocarditis as the cause of death is formulated by deduction, causing error and misleading the correct temporal evaluation of pathological events. We reviewed the literature realizing that histomorphological data are scarce and often poorly documented. Only after COVID-19 have the histomorphological aspects of myocarditis been better documented. This is due to poor autopsy practice and poor accuracy in identifying the specific histotype of myocarditis with identification of the responsible agent. We believe that four points are essential for a better understanding and complete diagnosis of the disease: (1) clinical classification of myocarditis; (2) etiological classification of myocarditis; (3) pathophysiology of viral and bacterial infections with host response; and (4) histopathological diagnosis with precise identification of the histotype and pathogen. In the review we provide histological images from authoritative scientific references with the aim of providing useful information and food for thought to readers.